Doing fieldwork - Pole, Christopher J. (Christopher John) (Sage, 2016)
This is not yet another step-by-step guide to research methods. Rather, Pole and Hillyard draw the reader into fieldwork as a form of living and lived research. They take key threads of research practices and processes and weave them into a holistic approach to fieldwork. Doing Fieldwork is a must read for new researchers planning a journey into the immersion of ′being there′ that is field work." - Professor Garry Marvin, University of Roehampton